2022
DOI: 10.35445/alishlah.v14i3.1595
|View full text |Cite
|
Sign up to set email alerts
|

A Multicultural Interactive Digital Book: Promoting Tolerance and Multiculturalism to Elementary School Students

Abstract: This study aimed to develop a multicultural interactive digital book for higher grade students of elementary school to promote tolerance and multiculturalism. The research used Research and Development method with ADDIE design that contained five steps: analyzing, designing, developing, implementing, and evaluating. First, the need analysis was conducted to find out what kind of literature can help students learn tolerance and multiculturalism. Next, the product was designed based on students' needs and charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
1
4
0
5
Order By: Relevance
“…Kagan, pointed out that collaborative learning between group members improves, and students feel more valued (Ismiyanti, 2020). The studies mentioned earlier have similar research results to previous studies Gillies, Nhu-Le, Vaughan, Zain, Subramaniam, Rashid & Ghani, which have shown that cooperative learning promotes advanced learning skills, better relationships among students, feeling more valued, and better learning attitudes (Cahyaningtyas et al, 2022). In summary, cooperative learning should be used effectively to increase students' engagement in learning to obtain better learning outcomes.…”
Section: Background Of the Studysupporting
confidence: 77%
See 1 more Smart Citation
“…Kagan, pointed out that collaborative learning between group members improves, and students feel more valued (Ismiyanti, 2020). The studies mentioned earlier have similar research results to previous studies Gillies, Nhu-Le, Vaughan, Zain, Subramaniam, Rashid & Ghani, which have shown that cooperative learning promotes advanced learning skills, better relationships among students, feeling more valued, and better learning attitudes (Cahyaningtyas et al, 2022). In summary, cooperative learning should be used effectively to increase students' engagement in learning to obtain better learning outcomes.…”
Section: Background Of the Studysupporting
confidence: 77%
“…Slavin emphasizes better learning outcomes with whole-group cooperative efforts (Ismiyanti, 2016). Few previous study, such as one conducted by Heleen dan Arnold, found that students in groups have better cooperation and engagement can solve problems together more effectively (Cahyaningtyas et al, 2022). By helping each other, students create a collaborative community that better enhances each member's performance.…”
Section: Discussionmentioning
confidence: 99%
“…Selain menjadi sebuah keuntungan keragaman tersebut juga menjadi sebuah tantangan bagi masyarakat Indonesia (Hidayati Azkiya et al, 2022). Seluruh masyarakat Indonesia haruslah menjunjung tinggi nilai-nilai toleransi supaya hidup berdampingan dengan damai antara satu dengan yang lainnya (Cahyaningtyas et al, 2022). Namun sayang, pada realitanya sering terjadi sikap intoleran terutama dalam konteks agama.…”
Section: Pendahuluanunclassified
“…Hal ini diyakini bahwa perbedaan yang berarti dibuat oleh blended learning dalam istilah kemandirian belajar bertumbuh dari sebuah perencanaan yang lebih baik dan penggunaan internet secara komprehensif dan efektif. (Cahyaningtyas et al, 2022).…”
Section: Pelaksanaan Pembelajaran Blended Learning DI Kelas Iv Sdn 04...unclassified